A new version of ElGamal signature scheme - Eddie Shahril Ismail; Yahya Abu Hasan (Universiti Kebangsaan Malaysia, 2006)
In the original ElGamal signature scheme and it’s variants, two secret integers-private key and one-time secret key are required to produce a signature on a message, m. The private key of a system will be used throughout the life of the system whereas the one-time secret key only be used once and must be regenerated (different one-time secret key) when signing different message. This paper introduces a new version of ElGamal signature that eliminates the use of one-time secret key. This property will make all attacks, aiming at revealing the one-time secret key irrelevant. The scheme also can be regar